PENANAMAN NILAI-NILAI KARAKTER ANTI KORUPSI PADA PEMBELAJARAN KIMIA - Jarwandi Jarwandi; Heldy Ramadhan Putra Pembangunan (Academy of Education Journal, 2022)
The purpose of this study was to determine the role of the world of education in preventing corruption through inculcating anti-corruption values ​​in the curriculum. The method used in this article is a qualitative method. Judging from the type, this article is a literature review. From the research, the results show that the instilling of anti-corruption character values ​​in the curriculum can be implemented at every level of education, and can be implemented in all subjects with due regard to management, principles and principles of the curriculum. Anti-corruption in chemistry learning in schools can be implemented by inserting each lesson, the Problem Basic Learning (PBL) approach model, making LKPD with the ADDIE approach model, the ethnoscience approach, integrating chemistry material with increasing faith and piety, instilling religious attitudes by inserting verses of the Koran and the Prophet's Hadith on learning materials, strong cooperation of all stakeholders to create conducive conditions.